Memory effects in backscattering of two-dimensional electrons in corrugated systems - Choque, Nilo Maurício Sotomayor (2006)
It is reported a theoretical and numerical study of non-markovian memory effects in backscattering of ballistic electrons constrained to move in a corrugated surface topography. Two approaches to model the electron trajectories are used, better approximation is obtained with the Hamilton-Dirac method for constrained system.